A Review of the Recreational Benefits of Cultural Ecosystem Service (CES) Indicators in the Urban Area - Kaede Chan Lip Chung; Andy Russel Mojiol (UCTS Publisher, 2018)
Cultural ecosystem services (CES) are the intangible, invisible, and non-consumable benefits of the ecosystem to human welfare. Nevertheless, due to the not a practical conceptual framework, there are lacking information on CES studies in the urban area. So, the aim of this paper systematically analyzes the works of literature on the recreational benefits of CES. A total of 38 journal paper systematical analysis found that MEA and TEEB are often to be used rather than CICES because it is still new in this field. Moreover, a total of 23 indicators indicate the value of recreation in the green space. Recreation should define as the natural landscape of people's preference for spending their leisure time interacting with physical and experiential facilitating outdoor activities to promote health and enjoyment. Subsequently, this study can also conclude that non-monetary assessments are the best approach to conducting empirical studies of CES. Simultaneously, in-depth studies are needed to look at the feasibility of these indicators for the ecosystem of the global.